Combined Expression of c-jun, c-fos, and p53 Improves Estimation of Prognosis in Oral Squamous Cell Carcinoma. (13th September 2016) - Wang, Shan; Xu, Xin; Xu, Fei; Meng, Yan; Sun, Changsheng; Shi, Lei; Zhao, Eryang
ABSTRACT: To identify the prognostic value of c-jun, c-fos, and p53 in oral cancer, we examined the impact of immunohistochemical expression of these markers on tumor progression in 157 oral squamous cell carcinoma (OSCC). We found that c-jun or c-fos was significantly associated with lymph node metastasis, and coexpression of c-jun/c-fos, or c-jun/c-fos/p53 were significantly associated with lymph node metastasis, poor differentiation and clinical stage. The coexpression of c-jun/c-fos/p53 was identified as independent prognostic factors for overall survival. Simultaneous coexpression of these markers in OSCCs might prove to be a useful indicator for differentiation of low and high-risk patients.